The Effect of Water Temperature on the Respiration Rate of Cyprinus carpio L. - Darmadi Goenarso (Journal of Mathematical and Fundamental Sciences, 1984)
Abstract. A study on the influence of alteration of water temperature on the respiration of a carp, Cyprinus carpio L. was performed. Oxygen consumption was measured by the continuous-flow technique. All fishes used in this experiment were acclimatized to 200C. It revealed that increasement of water temperature to 300C would caused the oxygen consumption of a fish to increase. Sari. Telah dilakukan penelitian pengaruh perubahan suhu air terhadap pernapasan ikan mas, Cyprinus carpio L. Pengukuran penggunaan oksigen dilakukan dengan teknik air mengalir. Ikan yang dipakai dalam percobaan ini diaklimatisasikan pada suhu 20'C. Hasil percobaan menunjukkan bahwa kenaikan suhu air hingga 30'C menyebabkan pertambahan penggunaan oksigen pada ikan.